Beanstalk Company business plan on urban farming using SNAP hydrophonics technology - Tolentino, Francis; Dayco, Rolando P. (Quezon City University of the Philippines Diliman, Technology Management Center, 2012)
The Beanstalk Company is an agri-business institution that will be engaged in urban farming. Managed by and registered under the Philippine law as a sole proprietor, Beanstalk Company will acquire and harness SNAP (Simple Nutrients Addition Program) hydroponics technology as its method of urban farming and as its core technology for developing and producing its crops. The company's main business is to distribute its crop produce directly to consumers and mainly to small and medium businesses within a 15 kilometer radius of its farm located in Cainta, Rizal. On its launch, the company will position itself as a product specialist supply chain with a flexible distribution structure which would mean it will focus producing lettuce and its common and marketable variety as the company's main product and produce.
Beanstalk Company will utilize SNAP hydroponics technology which poses to be the hydroponics technology system designed to meet the need for a low-cost urban farming on which most of the material used are low cost or recycled materials- This will enable the company to minimize and stabilize lettuce product cost and produce a stable supply of lettuces all year round even on various weather conditions. Large supplier and distributor of vegetable products in the Philippines mostly rely heavily on traditional farming method or farming on soil which have several disadvantages compared to hydroponics farming on which the Beanstalk Company will utilize to create as leverage in entering the market.
The demand for vegetable in the Philippines is growing and the trend of increasing consumption on healthy foods is arising. This development can be distinctly seen as the increase of salad varieties as lettuces can be found in many restaurant menus. Yet looking into these small and medium restaurants, hotels/motels and supermarkets there are limited or no lettuce suppliers that tends to them and serves them directly. The Beanstalk Company's business model will leverage on this opportunity. It will mainly directly distribute its products on wholesale with a stable long term price and supply of lettuce on business establishments as restaurants and hotels/motels and also brand it lettuce products on supermarkets within the 15 kilometer radius of its farm in Cainta, Rizal. A 15 Km radius of the farm would mean that the said business establishments of areas of Rizal, Antipolo City, Marikina City, Pasig City and Quezon City are the focus geographic areas of distribution of Beanstalk Company. Combined total targeted businesses of these areas will consist of 3563 businesses of which some 20 percent or 723 customers will be assumed as the market share that the company will capture on its first year of operations.
One of the key elements of Beanstalk Company's competitive strategy is to create a stable long term pricing that will be standard pricing for all market distribution channels. The lettuce products will be strategically priced at 180 pesos per kilo across all channels which is relatively lesser than current competitor prices in the market.
Furthermore, in maintaining the company's position of stable long term price and all year long supply of lettuce products it will leverage its use of SNAP hydroponics technology to sustain its low cost method of producing the crop products even on unfavorable weather conditions for farming. With this, bringing the products and the farm closer to the market will minimize labor and delivery cost compared to traditional farms who are mostly located outside or at the outskirts of Metro Manila-an advantage seen by developing an urban farming method system. Developing a hydroponics technology based farm on the other hand also poses advantages over traditional farming such as eliminating soil based pest and controlled growth environment for the crops to name a few on which the company also considers as a competitive advantage.
The Beanstalk Company will be owned and operated by an experienced individual under the counsel and tutelage of the SNAP technology proprietors who are in themselves seasoned agricultural field experts. The company will operate on a minimal number of regularly reporting employees apart from the company owner who will act as the project manager that will oversee all aspects of operation and sales. He will be joined together by one Delivery Man (in charge of delivering orders) and one Farm Specialist (in charge of hands-on farm maintenance) in running the business.
Beanstalk Company will be financed fully by the company owner using ones savings and loan from relatives (without interest). With a start-up investment of 664,746 pesos, the company projects to have its return on investment after 2 years and 3 months of operation. The company will have a 2 month conception phase before the actual launch of the company and will follow a strict systematic schedule of growing the crops to maintain its supply upon its business launch date. It also estimates that 5 percent growth in sales and market share per year will be added to the company's market portfolio.
In partial fulfillment of the requirements of TM 299
Keywords: Business planning; City planning; Hydroponics